Copper is required for oncogenic BRAF signalling and tumorigenesis. - Brady, D; Crowe, MS; Turski, M; Hobbs, G; Yao, X; Chaikuad, A; Knapp, S; Xiao, K; Campbell, S; Thiele, D; Counter, C (2014)
The BRAF kinase is mutated, typically Val 600→Glu (V600E), to induce an active oncogenic state in a large fraction of melanomas, thyroid cancers, hairy cell leukaemias and, to a smaller extent, a wide spectrum of other cancers. BRAF(V600E) phosphorylates and activates the MEK1 and MEK2 kinases, which in turn phosphorylate and activate the ERK1 and ERK2 kinases, stimulating the mitogen-activated protein kinase (MAPK) pathway to promote cancer. Targeting MEK1/2 is proving to be an important therapeutic strategy, given that a MEK1/2 inhibitor provides a survival advantage in metastatic melanoma, an effect that is increased when administered together with a BRAF(V600E) inhibitor. We previously found that copper (Cu) influx enhances MEK1 phosphorylation of ERK1/2 through a Cu-MEK1 interaction. Here we show decreasing the levels of CTR1 (Cu transporter 1), or mutations in MEK1 that disrupt Cu binding, decreased BRAF(V600E)-driven signalling and tumorigenesis in mice and human cell settings. Conversely, a MEK1-MEK5 chimaera that phosphorylated ERK1/2 independently of Cu or an active ERK2 restored the tumour growth of murine cells lacking Ctr1. Cu chelators used in the treatment of Wilson disease decreased tumour growth of human or murine cells transformed by BRAF(V600E) or engineered to be resistant to BRAF inhibition. Taken together, these results suggest that Cu-chelation therapy could be repurposed to treat cancers containing the BRAF(V600E) mutation.